P2Y 12 Inhibitor Monotherapy or Dual Antiplatelet Therapy After Complex Percutaneous Coronary Interventions - Gragnano, Felice; Mehran, Roxana; Branca, Mattia; Franzone, Anna; Baber, Usman; Jang, Yangsoo; Kimura, Takeshi; Hahn, Joo-Yong; Zhao, Qiang; Windecker, Stephan; Gibson, Charles M; Kim, Byeong-Keuk; et al. (Journal of the American College of Cardiology, 2023)
It remains unclear whether P2Y inhibitor monotherapy preserves ischemic protection while limiting bleeding risk compared with dual antiplatelet therapy (DAPT) after complex percutaneous coronary intervention (PCI). We sought to assess the effects of P2Y inhibitor monotherapy after 1-month to 3-month DAPT vs standard DAPT in relation to PCI complexity. We pooled patient-level data from randomized controlled trials comparing P2Y inhibitor monotherapy and standard DAPT on centrally adjudicated outcomes after coronary revascularization. Complex PCI was defined as any of 6 criteria: 3 vessels treated, ≥3 stents implanted, ≥3 lesions treated, bifurcation with 2 stents implanted, total stent length >60 mm, or chronic total occlusion. The primary efficacy endpoint was all-cause mortality, myocardial infarction, and stroke. The key safety endpoint was Bleeding Academic Research Consortium (BARC) 3 or 5 bleeding. Of 22,941 patients undergoing PCI from 5 trials, 4,685 (20.4%) with complex PCI had higher rates of ischemic events. The primary efficacy endpoint was similar between P2Y inhibitor monotherapy and DAPT among patients with complex PCI (HR: 0.87; 95% CI: 0.64-1.19) and noncomplex PCI (HR: 0.91; 95% CI: 0.76-1.09; P = 0.770). The treatment effect was consistent across all the components of the complex PCI definition. Compared with DAPT, P2Y inhibitor monotherapy consistently reduced BARC 3 or 5 bleeding in complex PCI (HR: 0.51; 95% CI: 0.31-0.84) and noncomplex PCI patients (HR: 0.49; 95% CI: 0.37-0.64; P = 0.920). P2Y inhibitor monotherapy after 1-month to 3-month DAPT was associated with similar rates of fatal and ischemic events and lower risk of major bleeding compared with standard DAPT, irrespective of PCI complexity. (PROSPERO [P2Y12 Inhibitor Monotherapy Versus Standard Dual Antiplatelet Therapy After Coronary Revascularization: Individual Patient Data Meta-Analysis of Randomized Trials]; CRD42020176853).